Strengthening Character Education Values for Santris in Pondok Pesantren - Jalaluddin Jalaluddin; Ulfiah Ulfiah; Agus Mulyanto; Sayid Muhammad Rifki Noval (UIN Sunan Gunung Djati Bandung, 2021)
Character education is an educational process that focuses on changing attitudes and behavior on an ongoing basis and always harmonizes them in life in accordance with the norms and values that they believe in. One of the vehicles for character building and development is Pondok Pesantrens. This research is motivated by changes in the behavior of santris who are not in accordance with what is expected by the Pesantren institution. The focus of this research is on how to strengthen the values of character education for santris. In particular, the purpose of this research is to find out about: 1) The objectives and programs for strengthening the character education values of Santri; 2) Implementation of Planning, Implementation, and Evaluation of the Strengthening of Santri character education values; 3) Problems faced in strengthening the character education values of Santri; and 5) Solutions to problems in strengthening Santri character education values. This research uses the approach qualitative method with descriptive method which was carried out at the Pondok pesantren Al-Masthuriyah and the Pondok pesantren Salafiyah in Sukabumi. Data collection techniques were carried out through field observations, interviews, and documentation studies. The grand theory of this research uses the theory of character education according to Thomas Lickona. Inductive data analysis resulted in several conclusions: 1) Objectives and Programs for Strengthening the Character Education Values of Santri at Pondok pesantren Al-Masthuriyah and Pondok pesantren Salafiyah, exist and are implemented, 2). Implementation of the Planning, Implementation, and Evaluation of the Program for Strengthening the character education values of Santri at the Pondok pesantren Al-Masthuriyah, has been planned, implemented and there is an evaluation. While at the Pondok pesantren Salafiyah there is a limited planning, implementation and evaluation classically, 3). Problems faced in strengthening the character education values of Santri at Pondok pesantren Al-Masthuriyah in the effectiveness of implementing the rules and educational background of heterogeneous coaches and teachers, while problems at Pondok pesantren Salafiyah in the independence of santris, religious santris, social society and santris' national insight . 4). Solutions to problems in strengthening the values of character education for santris at the Pondok pesantren Al-Masthuriyah through deliberation, santri development and personal approaches as well as equalizing perceptions. Meanwhile, the solution to the problems at the Pondok pesantren Salafiyah is through fostering succession, habituation in worship, habituation in santri activities, as well as national strengthening activities. The recommendations of this research for Pondok Pesantrens should be strengthened in the management of Pondok Pesantrens and for the Pondok Pesantren section of the Ministry of Religion of Sukabumi Regency to carry out managerial facilitation in accordance with regulations and their main functions. The research products produced in strengthening the character values of santris are strengthening: Tradition, Literacy, Independence, and National Attitudes.